Дослідження ансамблів складених псевдовипадкових послідовностей на базі функцій Уолша та Лежандра - Довбня, А. А. (ХНУРЕ, 2019)
Orthogonal and correlation properties of the complex binary sequences that are based on Legendre sequences, providing large ensembles and acceptable correlation properties, and Walsh sequences that provide orthogonal properties were analyzed.